Structure and Properties of Polymers Prepared by Polymerization of 2,2-Dimethyl-1,3-Propandiol and Îµ-Caprolactone Monomer - I Made Arcana; M. Hasan; Shinta Dewi Anggraini; Asti Ardhyo Febrianti; Aditya Ardana (Journal of Mathematical and Fundamental Sciences, 2009)
Poly(Îµ-caprolactone) (PCL) is very attractive synthetic polymer due to its properties, such as a high permeability, the lack of toxicity, and also biodegradability. However, it has limited application because of low melting point (60 °C), high crystallinity, and brittleness. The aim of the experiments is designed to improve the properties of PCL by formation of their polymers with 2,2-dimethyl-1,3-propandiol monomers with various chain length as a raw material to prepare poly(urethane-ester). These polymers were synthesized by a ring-opening polymerization of 2,2-dimethyl-1,3-propandiol and Îµ-caprolactone monomers in various composition in the presence of 1-hydroxy-3-chloro-tetraisobuthyldistanoxane as a catalyst. Polymers were characterized by analysis of functional groups (FTIR), microstructure (1H and 13C NMR), viscosity, hydroxyl number, and also melting point of polymers (DSC). Based on the structure analysis indicate that polymerization of 2,2-dimethyl-1,3-propandiol and Îµ-caprolactone monomers produced polymers with various molecular weights, which depend on the ratio of Îµ-caprolactone / 2,2-dimethyl-1,3-propandiol used in polymerization. The reactivity of CL monomer decreases to the active site of polymers with longer chain size. The melting points of polymers increase with the increasing of Îµ-caprolactone composition used in polymerization, whereas hydroxyl number decreases.